Leaving no one behind: Is the achievement of the Sustainable Development Goals possible without securing the dignity, rights, and well‐being of those who are “invisible”? - Anastasi, Erin (Int J Gynaecol Obstet, 2020)
The persistence of obstetric fistula—a devastating childbirth injury occurring largely among poor, marginalized women and girls—constitutes a human rights violation and a public health crisis. The Sustainable Development Goals (SDGs) aim to “leave no one behind.” Failing to eliminate fistula jeopardizes attainment of several of the SDGs. Member States of the United Nations adopted a UN Resolution on ending fistula in 2018, calling for an end to fistula within a decade. Building upon recommendations of the UN Secretary General's 2018 Report on Obstetric Fistula, the Resolution calls for significantly increased commitments and investments to end fistula. Crucial interventions for eliminating fistula include high‐quality, equitable, accessible health systems; implementing costed national strategies for eliminating fistula; integrating fistula into national plans to achieve the SDGs; strengthening national fistula task forces; and significantly increased, sustained financial support. Fistula elimination necessitates protecting women's/girls’ human rights and addressing social determinants that affect women's/girls’ ability to “survive, thrive and transform,” including social and economic inequities; gender‐based violence; child marriage and early childbearing; and access to education. Enhanced awareness‐raising and advocacy; improved research, data, monitoring and evaluation; holistic social reintegration and survivor empowerment; and community engagement are additional key strategies for realizing this ambitious goal.